Caring for people living with motor neuron disease: a qualitative study of challenges and coping among informal caregivers in South Africa - Allan, Bailey Claire Isabella (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.